Improvement of coal seam gas drainage by under-panel cross-strata stimulation using highly pressurized gas. (July 2015) - Lu, Tingkan; Wang, Zhaofeng; Yang, Hongming; Yuan, Pengju; Han, Yabei; Sun, Xiaoming
Abstract: Directed at creating fractures and extracting methane in low permeability, high gas-outburst coal seams, this paper presents the results of a comprehensive integration trial of under panel cross strata drilling with a new coal seam stimulation technique: the Cardox system in a colliery located in a major high gas content and outburst prone coal field in the central part of China. On the basis of the coal seam parametric measurements, the precise designation of under panel cross strata borehole patterns and the arrangement of the fracturing and monitoring procedures, the advantages of the Cardox system in creating fractures and improving gas drainage efficiency of low permeability coal seams are: (1) Changing the trend of gas concentration and/or pure gas quantity over time; (2) Maintaining the uptrend of gas concentration and/or pure gas quantity in a relatively long time period, which, in the current case, is ninety days and counting; and (3) Elevating gas drainage to a higher level. Stimulation mechanisms of the highly pressurized gas system have been proposed, and based on these mechanisms, the crushing and fracturing radii created by the highly pressurized gas have been calculated and corroborated well with the field monitoring data.